Cerebral Abnormalities in Duchenne MD - J Gordon Millichap; John J Millichap (Pediatric Neurology Briefs Publishers, 2014)
Investigators from Leiden University, the Netherlands, used quantitative MR imaging to study brain microstructure in 30 patients with Duchenne muscular dystrophy (DMD) and 22 age-matched controls (age 8-18 years).